PRODUCTIVE PERFORMANCE IN PIGS SUPPLEMENTED WITH INCREASING LEVELS OF ORGANIC SELENIUM - Valera Lara, Fabian; Estrada Gijón, Michelle; Sanginés García, José; Vite Aranda, Adelfo; Chay Canul, Alfonso Juventino; Vargas Bello Pérez, Einar; Piñeiro Vázquez , Angel (Chilean Journal of Agricultural & Animal Sciences, 2024)
The objective of this study was to determine the productive performance of pigs, during the starter (from 11 to 25 kg of live weight) and grower (from 25 to 50 kg of live weight) stages, supplemented with increasing levels of dietary organic selenium under tropical conditions. Pigs (n=71) were distributed in randomized block design with four treatments (0, 0.3, 0.6, and 0.9 mg kg-1 of feed). Organic selenium was included in the diet as selenomethionine (SeMet) from the BIOWAYS® product with a concentration of 2,000 ppm. The study was conducted over a 70-day period. The variables evaluated were voluntary feed intake, daily weight gain, and feed conversion. The daily weight gain varied between treatments in the starter stage, with average values of 0.431, 0.510, 0.466, and 0.554 g day-1 (P<0.05), but similar values of 0.890, 0.809, 0.908 and 0.884 kg day-1 were obtained in the grower stage for treatments with 0, 0.3, 0.6 and 0.9 mg kg-1 of feed, respectively. Feed conversion in the starter and grower stages improved when pigs were supplemented with selenium (P<0.05). Overall, supplementation with organic selenium improves daily weight gain and feed conversion in pigs during the starter and grower stages.